2022
DOI: 10.17358/ijbe.8.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Green Purchase: A Systematic Review and Future Research Agenda

Abstract: The purpose of this paper is to provide a holistic understanding of the contexts and theories applied in green purchase behavior studies. This research used PRISMA's systematic review method to analyze 76 empirical articles on green purchase intention and behavior from 2014 to 2019 across countries. This research is one of the first studies to cross-examine the context and theories applied in green purchase studies. For each theory applied, we present a brief description and recommendation for the future agend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The theory of planned behavior (TPB) has been widely applied in various research contexts, including research on the purchase intention of organic products (Wibowo et al 2022). The meta-analysis study by Han and Stoel (2017) concluded that the three predictors of intention in the TPB had a predictive power of 39.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of planned behavior (TPB) has been widely applied in various research contexts, including research on the purchase intention of organic products (Wibowo et al 2022). The meta-analysis study by Han and Stoel (2017) concluded that the three predictors of intention in the TPB had a predictive power of 39.7%.…”
Section: Introductionmentioning
confidence: 99%